Kajian Program Pengembangan dan Pemberdayaan Masyarakat Dalam Pelaksanaan Community Development (COMDEV) Di PT.Sugih Alamanugroho Di Desa Bedoyo Kecamatan Ponjong Kabupaten Gunung kidul Daerah Istimewa Yogyakarta - Mely Pebriani; A.A. Inung Arie Adnyano; Shilvyanora Aprilia Rande (Retii, 2022)
Sugih Alamanugroho is a company engaged in limestone mining located in Bedoyo Village, Ponjong District, Gunung Kidul Regency, Special Region of Yogyakarta. the impact of mining activities as a form of corporate responsibility PT. Sugih Alamanugroho runs a community development and empowerment program that is implemented in 3 villages, in Ponjong District, Gunungkidul Regency, Special Region of Yogyakarta. The results of the distribution of questionnaires (random sampling) of 135 respondents. The purpose of this research is to examine the community development and empowerment programs that have been carried out by the company related to the guidelines for implementing community development and empowerment referring to KEPMEN ESDM No 1824/K/30/MEM 2018 which includes 8 aspects, namely, education, health, real income, economic independence, social culture, environmental management, institutional formation, infrastructure and knowing the success rate of community development and empowerment programs that have been carried out by the company by measuring the level of community knowledge, the level of community satisfaction with the improvement of the company's image. Based on the survey results, public knowledge of the PPM program carried out by PT. Sugih Alamanugroho got the "Good" category with an average of 3.09 or equivalent to 61.8%, for community satisfaction it was in the "Good" category with an average of 3.52 or equivalent to 70.4% while corporate image is in the “Good” category with an average of 3.50 or equivalent to 70%. Based on the results of The Structural Equation Modeling (SEM) method using AMOS software the results of community knowledge on community development and empowerment programs have an influence on increasing community satisfaction with a value of 0.07 and the level of satisfaction of community knowledge on community development and empowerment programs does not affect improving company image because it has the value of -0.05 and the level of community satisfaction with community development and empowerment programs influence improving the company's image with a value of 0.76 Keywords: Mining, Development and Empowerment Program, Perception, Satisfaction, Image